Comparison of the Effects of Using Self-regulation Theory and self-care Education on Medical Adherence in Patients Receiving Peritoneal Kidney Dialysis - Narges Sadeghi Zarmehri; Farzaneh Hassanzadeh; Nahid Aghebati; Farzaneh Sharifipour (Mashhad University of Medical Sciences, 2018)
Background: Medical adherence is critical to peritoneal dialysis (PD) success. Accordingly, the self-regulation approach plays a crucial role in disease management and treatment progress through the formation of an organized pattern of beliefs in patients. Aim: The purpose of this study was to compare the effects of self-regulation theory (SRT) and self-care training on medical adherence in patients on PD. Method: This randomized clinical trial was conducted on 60 patients receiving PD admitted to Imam Reza and Ghaem Dialysis Centers in, Mashhad, Iran, 2017. They were assigned into two groups of SRT and self-care training using a drawing method. Both groups received SRT or self-care training in two 25-30-min sessions during 2 weeks. Medical adherence was measured by the End-Stage Renal Disease Adherence Questionnaire at the pre-intervention phase, as well as 3 and 6 weeks later. Data analysis was performed using repeated measures analysis of variance in SPSS software, version 25. Results: Both groups were homogeneous considering demographic variables. The mean scores of medical adherence at the pre-intervention phase and 3 and 6 weeks later in the SRT group was 99.0±16.0, 83.9±14.9, and 80.8±15.0, respectively. These values were 87.4±8.6, 79.4±7.6, and 78.3±7.1 in the self-care training group, respectively. There was a significant difference between the groups regarding these (P